Higher hospitalization and mortality rates among SARS‐CoV‐2‐infected persons in rural America. Issue 1 (27th June 2022) - Anzalone, Alfred Jerrod; Horswell, Ronald; Hendricks, Brian M.; Chu, San; Hillegass, William B.; Beasley, William H.; Harper, Jeremy R.; Kimble, Wesley; Rosen, Clifford J.; Miele, Lucio; McClay, James C.; Santangelo, Susan L.; et al.
Abstract: Purpose: Rural communities are among the most underserved and resource‐scarce populations in the United States. However, there are limited data on COVID‐19 outcomes in rural America. This study aims to compare hospitalization rates and inpatient mortality among SARS‐CoV‐2‐infected persons stratified by residential rurality. Methods: This retrospective cohort study from the National COVID Cohort Collaborative (N3C) assesses 1, 033, 229 patients from 44 US hospital systems diagnosed with SARS‐CoV‐2 infection between January 2020 and June 2021. Primary outcomes were hospitalization and all‐cause inpatient mortality. Secondary outcomes were utilization of supplemental oxygen, invasive mechanical ventilation, vasopressor support, extracorporeal membrane oxygenation, and incidence of major adverse cardiovascular events or hospital readmission. The analytic approach estimates 90‐day survival in hospitalized patients and associations between rurality, hospitalization, and inpatient adverse events while controlling for major risk factors using Kaplan‐Meier survival estimates and mixed‐effects logistic regression. Findings: Of 1, 033, 229 diagnosed COVID‐19 patients included, 186, 882 required hospitalization. After adjusting for demographic differences and comorbidities, urban‐adjacent and nonurban‐adjacent rural dwellers with COVID‐19 were more likely to be hospitalized (adjusted odds ratio [aOR] 1.18, 95% confidence interval [CI], 1.16‐1.21 and aOR 1.29, CI 1.24‐1.1.34) and to die or be transferred to hospice (aOR 1.36, CI 1.29‐1.43 and 1.37, CI 1.26‐1.50), respectively. All secondary outcomes were more likely among rural patients. Conclusions: Hospitalization, inpatient mortality, and other adverse outcomes are higher among rural persons with COVID‐19, even after adjusting for demographic differences and comorbidities. Further research is needed to understand the factors that drive health disparities in rural populations.